(untitled) (World Economics and Finance Bulletin, 2023)
The article deals with the problems of education and use of information and communication technologies in development women’s entrepreneurship in developing countries and in countries with emerging market economy. Empowerment women in the field of vocational education and skills to use ICT is essential to enable women to meaningfully participate in economy of the country, as well as so that they can perceive entrepreneurship as a realistic career option.